Քեյս–Ստադի տեխնոլոգիայի կիրառումը «Սահմանադրական իրավունք» առարկայի դասավանդման գործընթացում - Միրզախանյան, Լիլիթ (Զանգակ հրատ.)
The application of case study technology while teaching Constitutional Rights as a discipline has been viewed in the article as a way of enhancing its efficiency. A sample of a lesson has been brought to demonstrate some useful ways of case study technology usage. В статье рассматриваются возможности применения технологии case study в процессе преподавания дисциплины «Конституционное право» как средства повышения эффективности обучения. Представлена модель урока с употреблением метода case study.
Keywords: Ուսուցման և դասավանդման մեթոդիկա